2001
DOI: 10.1108/eum0000000005989
|View full text |Cite
|
Sign up to set email alerts
|

Asthma knowledge and management in primary schools in south Essex, UK

Abstract: This study was designed to establish the levels of knowledge about the management of asthma among primary school teachers in South Essex. A total of 135 primary schools participated in a questionnaire survey, with data analysis being carried out on responses from 517 teaching staff. Findings showed that 47 per cent of respondents reported concern about dealing with a child suffering from asthma. Only 16.1 per cent felt confident in dealing with a child suffering from a severe asthma attack. Less than a third o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the United Kingdom, asthma UK recommends specific guidelines for school asthma policies 19 . However, lack of such policies is still notable in a number of schools 20‐22 . In addition to this, there are studies which have reported that teachers are not familiar with national guidelines on asthma management in schools or school policies 21,23,24 .…”
mentioning
confidence: 99%
“…In the United Kingdom, asthma UK recommends specific guidelines for school asthma policies 19 . However, lack of such policies is still notable in a number of schools 20‐22 . In addition to this, there are studies which have reported that teachers are not familiar with national guidelines on asthma management in schools or school policies 21,23,24 .…”
mentioning
confidence: 99%